Activity of Adesmia Boronioides Resinous Exudate Against Phytopathogenic Bacteria - Santander-Meyer, R (Taylor and Francis Ltd., 2021)
Resinous exudate obtained from the aerial parts of Adesmia boronioides Hook.f. were evaluated to determine anti-phytopathogenic effects. Briefly, resinous exudate was obtained by dipping fresh plant material in dichloromethane; chemical composition was determined by GC–MS; and minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) were evaluated against four phytopathogenic bacteria. Resinous exudate yield was 8.5% (resin/fresh plant), of which esquel-6-en-9-one (14.25%), esquel-7-en-9-one (5.86%), and veratric acid (2.59%) were the effective antibacterial compounds. Tested against Pectobacterium carotovorum subsp. carotovora, Erwinia amylovora, Bacillus subtilis, and Pseudomonas syringae, MICs and MBCs ranged from 16 to 128 µg/mL and 32–256 µg/mL, respectively. These results provide initial evidence that resinous bush A. boronioides is a new and alternative source of substances with agricultural interest. © 2019 Informa UK Limited, trading as Taylor & Francis Group.
Keywords: Adesmia boronioides; resinous exudate; phytopathogenic bacteria